Cognitive Errors and Psychological Resilience in Patients With Social Anxiety and Obsessive-Compulsive Disorder: A Cross-Sectional Study - Leila Salek Ebrahimi; Seyedeh Elnaz Mousavi; Banafsheh Gharraee; Jahangir Mohammadi Bytamar; Mohsen Saberi Isfeedvajani (Baqiyatallah University of Medical Sciences, 2019)
Background: Cognitive errors have been presented as effective factors in the creation and continuation of obsessive-compulsive disorder and social anxiety disorder. Psychological resilience is an important factor in the tolerance of cognitive errors. Objective: The present study aimed to compare cognitive errors and the psychological resilience of patients with social anxiety disorder and those with obsessive-compulsive disorder. Methods: This cross-sectional study investigated a total of 60 patients, 30 with social anxiety disorder and 30 with obsessive-compulsive disorder (OCD), seen at a hospital in Zanjan city, Iran, in 2017. Participants were aged between 15 and 50 years. Participants were chosen using convenience sampling and on the basis of psychiatrist diagnosis and structured diagnostic interviews (SCID-I, II) according to the inclusion and exclusion criteria. The Cognitive Errors Questionnaire (CET) and the Connor-Davidson Resilience Scale (CD-RISC) were used to assess the variables. Results: A significant difference was observed between the two patient groups in the cognitive errors components (P ≤ 0.05). In patients with OCD, the highest average rate of cognitive errors was related to catastrophizing and splitting error. In patients with SAD, the highest mean rate of cognitive errors was related to catastrophizing. There was no significant difference in psychological resilience between the two groups. Conclusion: Cognitive errors play an important role in OCD and social anxiety disorder (SAD). OCD patients were observed to make more cognitive errors than SAD patients. However, psychological resilience was equal between both groups.